2015
DOI: 10.1016/j.ejpb.2015.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle diffusion within intestinal mucus: Three-dimensional response analysis dissecting the impact of particle surface charge, size and heterogeneity across polyelectrolyte, pegylated and viral particles

Abstract: Multiple particle tracking (MPT) methodology was used to dissect the impact of nanoparticle surface charge and size upon particle diffusion through freshly harvested porcine jejunum mucus. The mucus was characterised rheologically and by atomic force microscopy. To vary nanoparticle surface charge we used a series of self-assembly polyelectrolyte particles composed of varying ratios of the negatively charged polyacrylic acid polymer and the positively charged chitosan polymer. This series included a neutral or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(104 citation statements)
references
References 35 publications
5
99
0
Order By: Relevance
“…For a nanoparticle to traverse mucus, it must possess desired surface characteristics to avoid adhesion and steric inhibition by the mucin fiber mesh. It has been demonstrated that poly(lactic-co-glycolic acid) (PLGA) and polystyrene particles functionalized with mucus inert polymers such as poly(ethylene glycol) (PEG) enhanced mucus transport in pig gastric mucus (Dawson et al, 2004; Griffiths et al, 2015), pig intestinal mucus (Abdulkarim et al, 2015; Groo et al, 2014), mouse vaginal mucus (Ensign et al, 2012b), human cervicovaginal mucus (Lai et al, 2007; Mert et al, 2012; Tang et al, 2009a; Xu et al, 2013a; Xu et al, 2015), human respiratory mucus (Schuster et al, 2013), cystic fibrosis (CF) sputum (Suk et al, 2011; Suk et al, 2009; Tang et al, 2009a), and bovine vitreous ex vivo (Xu et al, 2013b). Moreover, our group has previously demonstrated that carboxyl and amine-functionalized nanoparticles disrupt the mucus barrier and improve drug permeation up to 4.9-fold with 200 nm carboxyl-nanoparticles in porcine gastric mucus compared controls without particles (McGill and Smyth, 2010).…”
Section: Transmucosal Drug Deliverymentioning
confidence: 99%
“…For a nanoparticle to traverse mucus, it must possess desired surface characteristics to avoid adhesion and steric inhibition by the mucin fiber mesh. It has been demonstrated that poly(lactic-co-glycolic acid) (PLGA) and polystyrene particles functionalized with mucus inert polymers such as poly(ethylene glycol) (PEG) enhanced mucus transport in pig gastric mucus (Dawson et al, 2004; Griffiths et al, 2015), pig intestinal mucus (Abdulkarim et al, 2015; Groo et al, 2014), mouse vaginal mucus (Ensign et al, 2012b), human cervicovaginal mucus (Lai et al, 2007; Mert et al, 2012; Tang et al, 2009a; Xu et al, 2013a; Xu et al, 2015), human respiratory mucus (Schuster et al, 2013), cystic fibrosis (CF) sputum (Suk et al, 2011; Suk et al, 2009; Tang et al, 2009a), and bovine vitreous ex vivo (Xu et al, 2013b). Moreover, our group has previously demonstrated that carboxyl and amine-functionalized nanoparticles disrupt the mucus barrier and improve drug permeation up to 4.9-fold with 200 nm carboxyl-nanoparticles in porcine gastric mucus compared controls without particles (McGill and Smyth, 2010).…”
Section: Transmucosal Drug Deliverymentioning
confidence: 99%
“…In humans, the ECM is an obstacle to drug delivery, as its mesh prevents large nanoparticles from penetrating deep into tissue or tumors. 1824 Mucus similarly controls the permeability of nanoparticles, 25,26 but can also limit diffusion of small molecules such as antibiotics.…”
Section: Introduction: Hydrogels Are Ubiquitous Selective Barriersmentioning
confidence: 99%
“…In line with this postulate, it has been show that the increment of hydrophobicity decreases the diffusion kinetics of nanoparticles in mucus. 38 …”
Section: Resultsmentioning
confidence: 99%